Active and Programmable Metasurfaces with Semiconductor Materials and Devices - Can Cui; Junqing Ma; Kai Chen; Xinjie Wang; Tao Sun; Qingpu Wang; Xijian Zhang; Yifei Zhang (Crystals, 2023)
Active metasurfaces provide promising tunabilities to artificial meta−atoms with unnatural optical properties and have found important applications in dynamic cloaking, reconfigurable intelligent surfaces, etc. As the development of semiconductor technologies, electrically controlled metasurfaces with semiconductor materials and devices have become the most promising candidate for the dynamic and programmable applications due to the large modulation range, compact footprint, pixel−control capability, and small switching time. Here, a technical review of active and programmable metasurfaces is given in terms of semiconductors, which consists of metasurfaces with diodes, transistors, and newly rising semiconductor materials. Physical models, equivalent circuits, recent advances, and development trends are discussed collectively and critically. This review represents a broad introduction for readers just entering this interesting field and provides perspective and depth for those well−established.